Optofluidic Planar Optical Cross-Connect Using Nematic Liquid-Crystal Waveguides - Tenghao Li; Qingming Chen; Xuming Zhang (IEEE Photonics Journal, 2018)
This paper proposes a compact planar optofluidic optical cross-connect (OXC) switch based on electro-optic (EO) waveguides in nematic liquid crystal (NLC). In the cross-bar fabric, each unit cell of the proposed device consists of two portions: the NLC EO waveguides for 1 × 2 switching and the fixed NLC-core waveguides to support subsequent beam paths of the lead-in/lead-out process or the bending process. With numerical simulations, a sample design of 8 × 8 OXC is analyzed and optimized, which provides the predicted broadband performance as approximately 8.0 dB maximum on-chip insertion loss, –45.9 dB cross-talk and 16 ms switching time in the footprint of 2 mm × 2 mm. The loss reduction and the switching speed-up issues are also discussed, with the expected 5.5 dB maximum on-chip insertion loss and 1 ms switching time. The proposed OXC switch is new in the working principle using both electric-field reconfigurable NLC waveguides and fixed NLC-core waveguides, and can leverage the liquid-crystal on silicon fabrication. It is potential for optical circuit switching in the small-scale data centers, or protection switching in optical communication networks.